CareTrack Australia: assessing the appropriateness of adult healthcare: protocol for a retrospective medical record review. Issue 1 (18th January 2012) - Hunt, Tamara D; Ramanathan, Shanthi A; Hannaford, Natalie A; Hibbert, Peter D; Braithwaite, Jeffrey; Coiera, Enrico; Day, Richard O; Westbrook, Johanna I; Runciman, William B
Abstract : Introduction: In recent years in keeping with international best practice, clinical guidelines for common conditions have been developed, endorsed and disseminated by peak national and professional bodies. Yet evidence suggests that there remain considerable gaps between the care that is regarded as appropriate by such guidelines and the care received by patients. With an ageing population and increasing treatment options and expectations, healthcare is likely to become unaffordable unless more appropriate care is provided. This paper describes a study protocol that seeks to determine the percentage of healthcare encounters in which patients receive appropriate care for 22 common clinical conditions and the reasons why variations exist from the perspectives of both patients and providers. Methods/design: A random stratified sample of at least 1000 eligible participants will be recruited from a representative cross section of the adult Australian population. Participants' medical records from the years 2009 and 2010 will be audited to assess the appropriateness of the care received for 22 common clinical conditions by determining the percentage of healthcare encounters at which the care provided was concordant with a set of 522 indicators of care, developed for these conditions by a panel of 43 disease experts. The knowledge, attitudes and beliefs of participants and healthcare providers will be examined through interviews and questionnaires to understand the factors influencing variations in care. Ethics and dissemination: Primary ethics approvals were sought and obtained from the Hunter New England Local Health Network. The authors will submit the results of the study to a relevant journal as well as undertaking oral presentations to researchers, clinicians and policymakers.